DGGG Guidelines Programme: Status Quo - Quo Vadis! - Beckmann, Matthias; Linde, I.; Buetof, C.; Kreienberg, R.; Gaß, Paul (Geburtshilfe und Frauenheilkunde, 2014)
The Guidelines programme of the German Society of Gynaecology and Obstetrics (DGGG) is an executive part of the DGGG Guidelines Commission. It includes in-house planning and organisation of all guidelines as well as representation outside of the DGGG. This article does not concern the development of the guidelines as much as it concerns the planning, organisation, registration, editing and publication of the guidelines in context of the DGGG Guidelines programme. It targets interested parties, especially authors and coordinators of guidelines.
EVALuna2:17455